Multicast-unicast key management scheme in IPv6 networks - Mehdizadeh, Abbas; Hashim, Fazirulhisyam (2014)
Key management is one of the key security issues in multicast IPv6 networks. To achieve secure communications in such networks, a reliable and competent key management scheme should be imposed and implemented. Whenever a new node is accepted to join or leave the network, a new key should be generated and distributed to every nodes in the multicast group. Inadequately, this approach increases the number of keys transmitted (communication cost) of the key management. While a number of algorithms has been proposed to address this issue, most of them have severely affected the computation cost (i.e., number of key encryption, decryption, and derivation) of the key management. By concentrating on communication and computation costs, we give prominence to the possibility of addressing the both costs without having to sacrifice one for the sake of the other. In this paper, we propose a lightweight key management scheme for IPv6 networks, which is capable of reducing both communication and computation costs. The performance evaluation demonstrates the efficiency of our proposed method in comparison with the existing ones in reducing such costs, while at the same time maintaining both forward and backward securities.